OPTIMIZING THE SUPERVISORY FUNCTION OF THE REGIONAL PEOPLE'S REPRESENTATIVE COUNCIL OF MUSI BANYU ASIN REGENCY IN 2025 - Supriyadi; Ardiyan Saptawan; Raniasa Putra (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the optimization of the oversight function of the Musi Banyuasin Regency Regional People's Representative Council (DPRD), which in practice still tends to be ceremonial and has not yet addressed the substantive aspects of regional government administration. Effective oversight is a key pillar in realizing good governance, particularly in ensuring executive accountability, transparency, and responsiveness to the public interest. This study uses a qualitative approach with a case study method, allowing researchers to delve deeply into the dynamics of the DPRD's oversight function. Data were collected through in-depth interviews, observations, and a review of relevant official documents, then analyzed using the Good Governance theoretical framework. The results indicate that the effectiveness of the Musi Banyuasin Regency DPRD's oversight function still faces various structural and political obstacles. The main obstacles include low levels of transparency and information disclosure from the executive branch, limited human and institutional capacity within the DPRD, and strong political pragmatism that impacts oversight of independence. Furthermore, this study also identified supporting factors, particularly increasing public pressure and control through the media and civil society, that have encouraged the DPRD to carry out its oversight function more actively. Based on these findings, this study formulates several strategic recommendations focused on strengthening the institutional capacity of the Regional People's Representative Council (DPRD), increasing the use of information technology in the oversight process, and institutionalizing public participation as a partner in oversight. This strategy is expected to encourage a more effective, substantive, and good governance-oriented DPRD oversight function, supporting accountable regional governance by 2025.